2015
DOI: 10.1155/2015/810134
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Oncological Value of Preoperative BMI in Gastric Cancer Patients: A Single Center Experience

Abstract: Introduction. The impact of preoperative BMI on surgical outcomes and long-term survival of gastric cancer patients was investigated in various reports with contrasting results. Materials & Methods. A total of 378 patients who underwent a surgical resection for primary gastric cancer between 1994 and 2011 were retrospectively studied. Patients were stratified according to BMI into a normal group (<25, group A), an overweight group (25–30, group B), and an obesity group (≥30, group C). These 3 groups were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
13
2
Order By: Relevance
“…BMI was higher in P2 than in P1, and some studies report that BMI could be an independent factor for long-term survival after surgical treatment for gastric cancer (27,28). In our study, the average BMI difference between the two periods was only 0.5, and Voglino et al suggested that BMI does not affect postoperative complications or long-term survival (29).…”
Section: Discussioncontrasting
confidence: 43%
“…BMI was higher in P2 than in P1, and some studies report that BMI could be an independent factor for long-term survival after surgical treatment for gastric cancer (27,28). In our study, the average BMI difference between the two periods was only 0.5, and Voglino et al suggested that BMI does not affect postoperative complications or long-term survival (29).…”
Section: Discussioncontrasting
confidence: 43%
“…A meta-analysis has demonstrated that high BMI was associated with increased risk of gastric cardia cancer [ 16 ]. The association between BMI and clinical outcomes of gastric cancer has also been widely investigated, however, it was still under debate [ 10 13 ]. Thus, the present study aims to investigate the impact of BMI on the clinical outcomes of gastric cancer after radical gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that BMI was associated with postoperative complications [ 4 ] and prognosis [ 11 ] of gastric cancer. However, no association between BMI and clinical outcomes of gastric cancer has also been reported [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) represents one of the most frequent neoplasia worldwide, and specifically the fourth and fifth most common cancer in men and women and the third and fifth cause of cancer-related death [1].…”
Section: Introductionmentioning
confidence: 99%